Does school matter for students' self-esteem? Associations of family SES, peer SES, and school resources with Chinese students' self-esteem. (February 2021) - Li, Weiwei; Zeng, Xihua; Wang, Yun; Curtis, Robin; Sparks, Erin
Highlights: Family SES (objective family income, parental education, subjective family income) positively related to self-esteem. Peer parental education, teacher-related resources positively related to self-esteem. Urban schools strengthened the positive association between subjective family income and self-esteem. Peer parental education level strengthened the positive association between parental education and self-esteem. Teacher education level buffered the positive association between parental education and self-esteem. Abstract: Educational equality has attracted many countries' efforts to increase school resources to improve poor students' nonachievement development. The present study investigated the associations between family socioeconomic status (SES) and self-esteem, as well as their variances across school contextual variables (school location, peer SES, school resources). This study used data from the National Children's Study of China (NCSC), with a sample of 23, 627 students (4th – 9th grade, mean age = 12.76 years, 47.1 % female) from 604 schools. The multilevel linear model analyses mainly found the following: (1) family SES (objective income, subjective income, parental education) was significantly and positively related to self-esteem; (2) peer parental education and teacher-related resources were positively and significantly associated with self-esteem; and (3) most importantly, the positive association between subjective income and self-esteem was stronger in urban schools than rural schools. The positive association between parental education and self-esteem was stronger in schools with higher peer parental education but was weaker in schools with higher teacher education. Based on these findings, we provide suggestions for the efficient allocations of school resources and the promotion of programs for students' self-esteem.